Needs Analysis of Competency-Based Training for Customer Service Representatives - Bella, Herlana Baaqi (Jurnal Manajemen Pendidikan, 2025)
Background Traditional training methods often emphasize generic content and may fail to address the specific competencies needed for effective performance in customer service roles. Consequently, there is a growing need for competency-based training (CBT) programs that align training objectives with actual job requirements and performance expectations. CBT focuses on developing specific skills, behaviors, and knowledge areas that are directly linked to job success. Purpose This study aims to analyze the need for competency-based training for Customer Service Representatives (CSR) at Bank Syariah Indonesia (BSI), especially in Region VI Bandung. Design/method/approach Using a descriptive-verification approach with a non-experimental method, data were collected through a Likert questionnaire from CSR Region VI Bandung. Cluster analysis and Mann-Whitney tests revealed that out of 12 competency indicators, there were 8 indicators (such as empathy, communication, and problem solving) that showed significant differences between the superior and average CSR groups. Results This study shows that eight core competencies such as empathy, communication, and problem-solving need to be improved through focused training to enhance CSR performance at Bank Syariah Indonesia. Contribution/value This study holds strategic value in designing data-driven CSR competency training to enhance service quality in Islamic banking.